Ultrastructure of the seminiferous tubules in oligoasthenoteratozoospermic men associated with varicocele. (30th August 2012) - El‐Kamshoushi, A. M.; Zohdy, N. I.; Abou Khedr, N. A.; Nabhan, S. A.; Mostafa, T.
Summary: Varicocele is associated with venous reflux that may cause increased heat and interstitial pressure within the testes, with variable pathological effects on spermatogenesis. This study aimed to study the ultrastructural testicular changes in the seminiferous tubules of 20 infertile severe oligoasthenoteratozoospermia (OAT) men associated with varicocele and five patients with obstructive azoospermia without varicocele as controls. They were subjected to testicular biopsy which was evaluated by transmission electron microscopy. Ultrastructurally, the seminiferous epithelium in the testicular biopsies of infertile severe OAT men associated with varicocele was variably affected in the form of thickening of the peritubular connective tissue, vacuolation of Sertoli cell and germ cell cytoplasm, presence of degenerated and apoptotic cells among the germinal epithelium, altered spermatids and abnormal spermatozoa. It is concluded that varicocele in severe OAT men is associated with ultrastructural changes in the seminiferous tubule.